Amyloid-ß and islet amyloid pathologies link Alzheimer disease and type 2 diabetes in a transgenic model. - Wijesekara, N.; Ahrens, R.; Sabale, M.; Wu, L.; Ha, K.; Verdile, Giuseppe; Fraser, P. (Federation of American Societies for Experimental Biology, 2017)
Alzheimer's disease (AD) and type 2 diabetes (T2D) present a significant risk to each other. AD and T2D are characterized by deposition of cerebral amyloid-ß (Aß) and pancreatic human islet amyloid polypeptide (hIAPP), respectively. We investigated the role of amyloidogenic proteins in the interplay between these diseases. A novel double transgenic mouse model combining T2D and AD was generated and characterized. AD-related amyloid transgenic mice coexpressing hIAPP displayed peripheral insulin resistance, hyperglycemia, and glucose intolerance. Aß and IAPP amyloid co-deposition increased tau phosphorylation, and a reduction in pancreatic ß-cell mass was detected in islets. Increased brain Aß deposition and tau phosphorylation and reduced insulin levels and signaling were accompanied by extensive synaptic loss and decreased neuronal counts. Aß immunization rescued the peripheral insulin resistance and hyperglycemia, suggesting a role for Aß in T2D pathogenesis for individuals predisposed to AD. These findings demonstrate that Aß and IAPP are key factors in the overlapping pathologies of AD and T2D.-Wijesekara, N., Ahrens, R., Sabale, M., Wu, L., Ha, K., Verdile, G., Fraser, P. E. Amyloid-ß and islet amyloid pathologies link Alzheimer disease and type 2 diabetes in a transgenic model.